Analisis Asuhan Keperawatan Dengan Penerapan Terapi SEFT Terhadap Kualitas Tidur dan Kecemasan Pada Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisa - Tarisya Meysal Sabila; Bayu Saputra (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2026)
Background: Patients with chronic kidney disease (CKD) undergoing hemodialysis at Arifin Achmad General Hospital in Pekanbaru often experience sleep disturbances and anxiety that require nonpharmacological interventions. One therapy that can be used is the Spiritual Emotional Freedom Technique (SEFT). Objective: to analyze nursing care and evaluate the application of SEFT therapy in improving sleep quality and reducing anxiety in CKD patients. Methods: This study used a single-subject case study design (Mrs. W). The instruments used included an observation sheet, the Pittsburgh Sleep Quality Index (PSQI) questionnaire, and the Hamilton Anxiety Rating Scale (HARS). The SEFT intervention was conducted outside of the hemodialysis schedule on December 9 and 10, 2025, for 15–30 minutes per session. Results: The results showed an improvement in sleep quality and a reduction in anxiety after two interventions, with an average sleep quality score of 1.5 and an anxiety score of 2. Conclusion: SEFT therapy can be considered as a nonpharmacological nursing intervention to help improve sleep quality and reduce anxiety in patients with CKD.